Importance of aspartyl protease 5 in the establishment of the intracellular niche during acute and chronic infection of Toxoplasma gondii. Issue 6 (4th November 2022) - Dogga, Sunil Kumar; Lunghi, Matteo; Maco, Bohumil; Li, Jiagui; Claudi, Beatrice; Marq, Jean‐Baptiste; Chicherova, Natalia; Kockmann, Tobias; Bumann, Dirk; Hehl, Adrian B.; Soldati‐Favre, Dominique; Hammoudi, Pierre‐Mehdi
Abstract: Virulence and persistence of the obligate intracellular parasite Toxoplasma gondii involve the secretion of effector proteins belonging to the family of dense granule proteins (GRAs) that act notably as modulators of the host defense mechanisms and participate in cyst wall formation. The subset of GRAs residing in the parasitophorous vacuole (PV) or exported into the host cell, undergo proteolytic cleavage in the Golgi upon the action of the aspartyl protease 5 (ASP5). In tachyzoites, ASP5 substrates play central roles in the morphology of the PV and the export of effectors across the translocon complex MYR1/2/3. Here, we used N‐terminal amine isotopic labeling of substrates to identify novel ASP5 cleavage products by comparing the N‐terminome of wild‐type and Δ asp5 lines in tachyzoites and bradyzoites. Validated substrates reside within the PV or PVM in an ASP5‐dependent manner. Remarkably, Δ asp5 bradyzoites are impaired in the formation of the cyst wall in vitro and exhibit a considerably reduced cyst burden in chronically infected animals. More specifically two‐photon serial tomography of infected mouse brains revealed a comparatively reduced number and size of the cysts throughout the establishment of persistence in the absence of ASP5. Abstract : Essential to establish a Toxoplasma gondii infection, a subset of GRAs proteins residing in the parasitophorous vacuole or exported into the host cell, undergo proteolytic cleavage in the Golgi via the aspartyl protease 5 (ASP5). Here, we extended the study of ASP5 roles in the bradyzoite stage and showed that ASP5 substrates are not translocated across the mature cyst wall and that these substrates might play a structural role in the maintenance of the cyst wall.